IMPLEMENTATION OF FUZZY LOGIC ON SPEED PREDICTION ON INCLUDING ROADS - Alghi Sawaludin; Rahmat Hidayat; Reni Rahmadewi (TEKNOKOM, 2023)
Going through a road with a high slope has a risk of an accident due to a miscalculation by the driver. Therefore, detecting the speed limit to pass it is the solution. The aim of this research is to create a precise and minimal error system that predicts the uphill speed that must be used by the driver. By using fuzzy logic, of course you can predict what speed should be used. For tilt detection, a gyroscope is used and speed detection is being used using a GPS sensor. For the fuzzy inference system itself, it uses the Takagi Sugeno-Kang, method with a linear and constant output. In addition, the calculation of the crisp value is carried out using the manual calculation method and using a simulation application, namely MATLAB. The results of subsequent calculations are compared to calculate the precision value of the system in detecting uphill speed. The calculation uses MAPE. So the results of this study are speed detection systems that must be used on inclines that predict precisely. The implication of this research is that driving safety on high-slope roads can be improved and accidents that occur can be minimized. In addition, the driver can estimate the speed that must be used.